A MARXIST APPROACH IN READING PERCY BYSSHE SHELLEYâ€™S â€œSONG TO THE MAN OF ENGLANDâ€ (EUFONI: Journal of Language, Literary, and Cultural Studies, 2019)
This study is aimed to uncover some Marxist issues in one famous poetry in Romantic period: Percy Bysshe Shelley's "Song to the Man of England". Shelley sees that life with hierarchy in social structure is not fair. The life of working class is so miserable. They work hard with all of their power, energy, time, and mind to serve the landlord. However, the working class never get a fair justice for their life. Some concepts of Marxism such as class struggle and alienation will be used as theoretical framework in this study. The result of the study shows that Shelleyâ€™s â€œSong to the Men of Englandâ€ represent the characteristic of romantic poem written by romantic poet which is full of the sanctity of imagination. It constructs an ideal world based on the contemplation of beauty. It tries to be the founder of civil society and the inventors of the arts of life. It tries to be a kind of prophecy which has ability to change the condition of politics, social, and spiritual life, especially the life of working class in England.Keywords: Marxism, Alienation, Percy Bysshe Shelley, Romanticism.